Social inclusion of LGBTQ and gender diverse adults with intellectual disability in disability services: A systematic review of the literature. Issue 1 (26th July 2021) - Smith, Elizabeth; Zirnsak, Tessa‐May; Power, Jennifer; Lyons, Anthony; Bigby, Christine
Abstract: Background: Lesbian, gay, bisexual, transgender, queer (LGBTQ) and gender diverse adults with intellectual disability experience exclusion within disability services. Objective: This review explores the experiences of social inclusion/exclusion of this cohort in the context of disability services. Search Method: A systematic search was conducted of peer‐reviewed research published between January 2014 and April 2019. Five databases returned 66 articles plus three from hand searches. Appraisal and Synthesis: Nine articles were included in this review. The Critical Appraisal Skills Programme tool was used to assess the quality of the research. NVivo 12 was used as a tool to organise the articles. Results: Marginalisation of LGBTQ adults with intellectual disability in western societies is mirrored in disability organisations. There remains a dearth of research into experiences of transgender people with intellectual disability who use disability services. Conclusions: Research into interventions that support the inclusion of this cohort in disability support services is needed.